Financial Performance and Total Resources: Trend and sensitivity Analysis of Indian Oil Exploration and Production Companies - Ali, Anis; Alhassun, Abdulrahman; Fatima, Nadeem (International Journal of Energy Economics and Policy, 2024)
The firms involved in the exploration and production (E&P) of natural gas resources and crude oil play a crucial role in the energy sector and contribute to the economy. Exploration and production refer to discovering, drilling, and extracting natural gas resources and crude oil from beneath the earth’s surface. Exploration and production firms provide a base for the downstream companies to make crude oil consumable. The financial performance of the downstream companies depends on the cost efficiency of the E&P firms. The purpose of the study is to determine the relationship between the total resources and measures of financial performance. The study is based on secondary data and financial ratios, index numbers applied to get the financial performance, and variability of financial performance. Correlation is used to get the trend and quick impact of variability on the total assets on the financial measures in the short and long run. The study found that while return on total resources is positively influenced in the long run, profitability based on sales and short-term paying ability is negatively governed by the absolute quantity of expansion of all available resources. Although the long-term association is positive, there is a short-term lag in the positive increase of the total resources on the ROA. Overall, based on their average absolute amount of total resources, relatively, the mutual study of the mean growth rate of all resources and financial indicators of Indian E&P explore negativity.